Analisis Dampak Dukungan Sosial Online terhadap Post Traumatic Growth pada Generasi Z sebagai Korban Dating Violence / Kekerasan dalam Pacaran (KDP) - Ningrum, Annisa Mukti; Nuqul , Fathul Lubabin (Psikodinamika: Jurnal Literasi Psikologi, 2026)
Generation Z, born between 1995-2010, faces unique challenges such as economic instability and mental health issues. Their presence in the real and virtual world influences their behavior, including the way they get social support, which now also comes from social media. This study uses the Systematic Literature Review method to analyze the role of online social support on post-traumatic growth in Gen Z victims of dating violence, as well as investigate the role of forensic psychology in dating violence cases. The purpose is to evaluate the effectiveness of online social support in the context of dating violence in Gen Z. The benefit of this study is to explain how the phenomenon of KDP in Gen Z can be studied through the perspective of online social support. The results of the study show that online social support plays an active role in facilitating post-traumatic growth in Gen Z dating violence victims. Keywords: Dating Violence Victim; Online Social Support; Post Traumatic Growth.